2010
DOI: 10.1016/j.neurobiolaging.2008.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor imaging of deep gray matter brain structures: Effects of age and iron concentration

Abstract: Diffusion tensor imaging (DTI) of the brain has become a mainstay in the study of normal aging of white matter, and only recently has attention turned to the use of DTI to examine aging effects in gray matter structures. Of the many changes in the brain that occur with advancing age is increased presence of iron, notable in selective deep gray matter structures. In vivo detection and measurement of iron deposition is possible with magnetic resonance imaging (MRI) because of iron's effect on signal intensity. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
172
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(195 citation statements)
references
References 68 publications
21
172
2
Order By: Relevance
“…In preterm infants with diffuse excessive high signal intensity in white matter indicating white matter abnormality, increased axial and radial diffusivity have been found on DTI (33). DTI studies of normal aging subjects have revealed higher FA and axial diffusivity in basal ganglia attributed to tissue degradation and a relatively more compact tissue (34). A restricted volume of basal ganglia has been shown in preterm infants (35), parallel to our findings of lower contralateral brain volume after HI in the long term.…”
Section: Dti and Memri Of Hi And Hyperoxiasupporting
confidence: 87%
“…In preterm infants with diffuse excessive high signal intensity in white matter indicating white matter abnormality, increased axial and radial diffusivity have been found on DTI (33). DTI studies of normal aging subjects have revealed higher FA and axial diffusivity in basal ganglia attributed to tissue degradation and a relatively more compact tissue (34). A restricted volume of basal ganglia has been shown in preterm infants (35), parallel to our findings of lower contralateral brain volume after HI in the long term.…”
Section: Dti and Memri Of Hi And Hyperoxiasupporting
confidence: 87%
“…Specifically, without a control group or histopathologic data we are unable to assess whether FA values of the deep GM reflected SVD pathology. In addition, because of the reported direct correlation between iron content and FA values, 12,42 age-related iron accumulation in the striatum might have concealed possible associations of FA changes in the caudate and putamen with WMH burden and accrual. There is emerging scientific evidence that the iron content increases with age also within the thalamus.…”
Section: Discussionmentioning
confidence: 99%
“…24 It has been reported that iron deposition influences DTI metrics 16,17 by introducing local field gradients that have been shown to increase anisotropy. 25 Pfefferbaum et al 16 reported increased anisotropy in deep gray matter nuclei with age and correlated it with FDRI estimates. A near-perfect correlation between FDRI estimates and brain iron concentration measured postmortem has also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…A near-perfect correlation between FDRI estimates and brain iron concentration measured postmortem has also been reported. 16,26 It suggests that iron accumulation influences FA values in controls and patients with abnormal iron metabolism. In another DTI study on brain hemorrhage and HBT, increased FA has been reported even in glioma with a chronic stage of bleed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation